A hidden pandemic? An umbrella review of global evidence on mental health in the time of COVID-19 - Bower, Marlee; Smout, Scarlett; Donohoe-Bales, Amarina; O’Dean, Siobhan; Teesson, Lily; Boyle, Julia; Lim, Denise; Nguyen, Andre; Calear, Alison L.; Batterham, Philip J.; Gournay, Kevin; Teesson, Maree (Frontiers in Psychiatry, 2023)
Background: The mental health impacts of the COVID-19 pandemic remain a public health concern. High quality synthesis of extensive global literature is needed to quantify this impact and identify factors associated with adverse outcomes. Methods: We conducted a rigorous umbrella review with meta-review and present a) pooled prevalence of probable depression, anxiety, stress, psychological distress, and post-traumatic stress, b) standardised mean difference in probable depression and anxiety pre-versus-during the pandemic period, and c) comprehensive narrative synthesis of factors associated with poorer outcomes. Databases searched included Scopus, Embase, PsycINFO, and MEDLINE dated to March 2022. Eligibility criteria included systematic reviews and/or meta-analyses, published post-November 2019, reporting data in English on mental health outcomes during the COVID-19 pandemic. Findings: Three hundred and thirty-eight systematic reviews were included, 158 of which incorporated meta-analyses. Meta-review prevalence of anxiety symptoms ranged from 24.4% (95%CI: 18-31%, I2: 99.98%) for general populations to 41.1% (95%CI: 23-61%, I2: 99.65%) in vulnerable populations. Prevalence of depressive symptoms ranged from 22.9% (95%CI: 17-30%, I2: 99.99%) for general populations to 32.5% (95%CI: 17-52%, I2: 99.35) in vulnerable populations. Prevalence of stress, psychological distress and PTSD/PTSS symptoms were 39.1% (95%CI: 34%-44%; I2: 99.91%), 44.2% (95%CI: 32%-58%; I2: 99.95%), and 18.8% (95%CI: 15%-23%; I2: 99.87%), respectively. Meta-review comparing pre-COVID-19 to during COVID-19 prevalence of probable depression and probable anxiety revealed standard mean differences of 0.20 (95%CI=0.07-0.33) and 0.29 (95%CI=0.12-0.45), respectively. Conclusions: This is the first meta-review to synthesise the longitudinal mental health impacts of the pandemic. Findings show that probable depression and anxiety were significantly higher than pre-COVID-19, and provide some evidence that that adolescents, pregnant and postpartum people, and those hospitalised with COVID-19 experienced heightened adverse mental health. Policymakers can modify future pandemic responses accordingly to mitigate the impact of such measures on public mental health.